2020
DOI: 10.1088/1748-605x/abb524
|View full text |Cite
|
Sign up to set email alerts
|

Sodium alginate-based composites as a collagen substitute for skin bioengineering

Abstract: The skin is a combination of two different types of tissue—epithelial and connective (mesenchymal). The outer protective layer of the skin, the epidermis, consists of multiple layers of keratinocytes residing on the basement membrane that separates them from the underlying dermis, which consists of a well-vascularized fibrous extracellular matrix seeded mainly by fibroblasts and mesenchymal stromal cells. These skin features suggest that the development of a fibroblast-friendly porous scaffold covered with a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Advances in regenerative medicine related to wound treatment have been studying the production of new nanostructured dressings that, in addition to serving as a protective barrier for the wound, maintain effective conditions to promote cell proliferation and migration [5,6]. Implementing intelligent and bioactive dressings, which have structures Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in regenerative medicine related to wound treatment have been studying the production of new nanostructured dressings that, in addition to serving as a protective barrier for the wound, maintain effective conditions to promote cell proliferation and migration [5,6]. Implementing intelligent and bioactive dressings, which have structures Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 99%
“…Bonding with scaffold materials with certain mechanical strength is required. The artificial dermal scaffold has good biocompatibility [ 28 ], suitable mechanical strength (can resist traction and shear forces) [ 29 ], and has a porous structure conducive to the progress of cell metabolism [ 30 ]. However, the current clinically used artificial dermal materials all have the disadvantage of insufficient vascular regeneration [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of IFI6 promoted cell proliferation and reduced apoptosis and ROS production after radiation [ 13 ]. Sodium alginate (SA) (a natural polysaccharide) has been used in biomedical tissue engineering because of its adhesiveness and biocompatibility [ 14 ]. Studies showed that SA-based hydrogels induced M2 polarization of macrophages in the inflammatory phase to reduce fibrosis and scar formation during skin regeneration [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%